Critical analysis of the human development index in Mesuji Regency, 2010–2022 - Suryanto, Sasmika Dwi; Mukhlis, Maulana; Makhya, Syarief; Rosalia, Feni (Goodwood Publishing, 2025)
Purpose: This study evaluates the performance of the Human Development Index (HDI) improvement program in the Mesuji Regency and identifies factors that influence the dynamics of HDI achievement. Mesuji is a peripheral region that experiences a significant socio-economic lag within Lampung Province, Indonesia. Research Methodology: This study employs a mixed method with an explanatory sequential design, combining quantitative analysis of HDI data from the BPS with qualitative interpretation of contextual and policy factors affecting HDI outcomes. Results: From 2010 to 2022, Mesuji’s HDI steadily increased, driven by improvements in Life Expectancy, Education Index, and Gross National Income per Capita. Key drivers include improved healthcare services, educational expansion, job availability, infrastructure development, and pro-poverty policies. Conclusions: The program aimed at increasing the Human Development Index (HDI) in Mesuji Regency has shown positive results from 2010 to 2022, yet the region's HDI remains classified as